System Engineering for Online Monitoring and Early Warning of Water Environment - Setiawan, Foni Agus; Sudriani, Yuli (INKOM Journal, 2015)
Measurement activity usually performed at a time or in a certain time period. In the case of measurements at one time, measurements manually by visiting the location of measurements, take measurements and write them down, then left the location is not a problem. However, measurements made within a certain period of time or year would be verydraining, costly, and time consuming if perfomed manually. Thus, design and implementation of embedded system for online monitoring and early warning of water environment is proposed. The system consists of two parts i.e. monitoring stations (site) and monitoring center (server). A monitoring station is an embedded system that has interface with a logger. Monitoring center is a computer that runs the service that gets the data sent by the monitoring stations, process it and put it into the database. Monitoring center also runan http service to display data acquired from monitoring stations to end users both in tabular or graphical view . The system can perform continuous measurements and its results can be monitored remotely.